2020
DOI: 10.1177/0268355520977294
|View full text |Cite
|
Sign up to set email alerts
|

Increased deep vein thrombosis cases during the COVID-19 quarantine

Abstract: Objective The aim of this study was to compare the number of deep vein thrombosis (DVT) cases during the quarantine period for COVID-19 to that of the last year. Methods This study was conducted as a single-center and retrospective study. All hospital admissions during April 2020 and May 2020 were screened from the hospital records, and DVT cases were recorded. Likewise, all hospital admissions during April 2019 and May 2019 were screened, and DVT cases were noted. DVT cases of both years were compared. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
2
0
1
Order By: Relevance
“…21 In a study done done in Italy, among 200 patients, 15% of patients with COVID-19 had DVT. 22 Similarly another study done in China has stated that 41.5% of patients with DVT were COVID positive patients. 23 A study done in Turkey amongst COVID-19 positive people in quarantine period, there was increased prevalence of DVT compared to normal population.…”
Section: Discussionmentioning
confidence: 94%
“…21 In a study done done in Italy, among 200 patients, 15% of patients with COVID-19 had DVT. 22 Similarly another study done in China has stated that 41.5% of patients with DVT were COVID positive patients. 23 A study done in Turkey amongst COVID-19 positive people in quarantine period, there was increased prevalence of DVT compared to normal population.…”
Section: Discussionmentioning
confidence: 94%
“…This study however suggested immobility, defined as quarantine in the study, as a compounding factor in patients who already had strong risk factors for VTE rather than prolonged seated immobility as an independent predictor on its own 9 . Secondly, a retrospective study by Karaali et al reported an increase in incidence of deep vein thrombosis (DVT) during its lockdown compared to the same period the year before (0.084% vs. 0.017%) and suggested that quarantine measures could have led to the increase 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Fatores que compõem à tríade de Virchowhipercoagulopatia, estase e lesão endotelial -são predisponentes para a TVP e devem ser investigados na história da doença. Além dos fatores de risco para TVP citados, história prévia de TVP, malignidade, história de cirúrgia, trauma, gravidez e obesidade foram observados em um estudo realizado na Turquia 19 . Um estudo realizado com pacientes diagnosticados com COVID-19 e que desenvolveram uma TVP, evidenciou que o principal acometimento vacular foi dos membros inferiores, sendo 34,8% em veias proximais e 65,2% em veias, havendo consenso entre os estudos sobre serem os membros inferiores a principal localização da TVP 20 .…”
Section: Discussionunclassified